Interacción física entre n-alcanos (1985)
Molecular properties of n-alkanes such as polarizability, number of dispersion electrons and infernal heat of vaporization are estlmated and expressed as functions of the number of groups that form the molecule. Since the ratio internal heat of vaporization to number of constituent groups is nearly constant for the n-alkanes from n-pentane to n-decane, a hypothesis regarding group properties is confirmed. Itis suggested that is possible to consider intermolecular attraction as a function of potential energy among groups. Geometric parameters from the cylindrical model proposed are given for each molecule. The group radii, interaction distances and attraction potential energy between similar molecules of n-alkanes are reported.